The Rape of Hylas in Theocritus Idyll 13 and Propertius 1.20 - Gyorkos, Andrew (My University, 2015)
The Hylas myth, in which the eponymous boy beloved of Heracles is raped by water nymphs while drawing water from a spring, seems to have been a wildly popular subject among the literary circles of Augustan Rome. Indeed the rape of Hylas had been so ubiquitous that Virgil himself could claim that no one was unfamiliar with it (Georgics 3.6: cui non dictus Hylas puer?). Yet despite this declaration, few renditions of the Hylas myth survive. Propertius 1.20, an Augustan era Latin poem in elegiac couplets, is one extant version of the rape of Hylas. While the similarities between this poem and Theocritus Idyll 13, a short Hellenistic hexameter poem composed well before Propertius, have long been observed by modern scholars, there has been no sustained effort to connect these two accounts of the Hylas myth conclusively. Instead, what little scholarly work that has been done on these poems either appraises them in isolation, or seeks a non-Theocritean template behind Propertius 1.20. With this thesis, I aim to prove definitively that Theocritus Idyll 13 is the major model for Propertius 1.20. In my first chapter, I provide a brief overview of the rape of Hylas throughout all of Greek and Latin literature. In my second chapter, I examine Theocritus Idyll 13 with particular attention to its wit, humour, and narrative. In my third chapter, I offer a thorough literary-critical appreciation of Propertius 1.20, establishing links to Idyll 13 wherever possible. Finally, in my conclusion, I consider the possible influence of other poets and mythographers upon Propertius, before appraising 1.20 both independently and within the context of the Propertian Monobiblos.
Keywords: Love Elegy; Hellensitic Poetry; Theocritus; Propertius; Literary Criticism; Augustan Literature; Heracles; Hylas